Norbert elias, social history and sport - Van Gestel, Joannes, author.
1 online resource (170 pages)
Keywords: In times when the social sciences have become increasingly fragmented and more focused on ‘the pieces of the puzzle’; the puzzle, as a topic in its own right, has slowly been moved towards the background. Nonetheless, as humanity becomes ever more globalized, there is a greater need for in-depth discussion on the theory behind the direction of humanity in history and the interrelationships between the different areas in which humans associate themselves with, including that of leisure and sport.